2023
DOI: 10.3390/ma16031071
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Cast Polyolefin Film Extrusion Technology for Multi-Layer Packaging Applications

Abstract: The review article presents the technology of producing polyolefin-based films by extrusion casting. Due to the wide use of this type of film as packaging for food and other goods, obtaining films with favorable properties is still a challenge for many groups of producers in the plastics market. The feedblock process and multimanifold process are the main methods of producing multi-layer film. In the case of food films, appropriate barrier properties are required, as well as durability and puncture resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 100 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…Here, we focus on the "structuring" polymer processing based on injection molding. Other "structuring" polymer processing methods have been reviewed by Peterlin 123 and An et al 124 on extrusion, Fu et al 125 and Dziadowiec et al 126 on film casting, and Xu et al 127 and Hufenus et al 128 on melt spinning. Based on conventional injection molding (CIM), a novel type of injection molding has been developed, which introduces a distinct melt flow feature during injection molding usually in the packing stage; i.e., the melt flow in the cavity of mold is manipulated by using pressure-driven flow.…”
Section: "Structuring" Polymer Processing Based On Ficpmentioning
confidence: 99%
“…Here, we focus on the "structuring" polymer processing based on injection molding. Other "structuring" polymer processing methods have been reviewed by Peterlin 123 and An et al 124 on extrusion, Fu et al 125 and Dziadowiec et al 126 on film casting, and Xu et al 127 and Hufenus et al 128 on melt spinning. Based on conventional injection molding (CIM), a novel type of injection molding has been developed, which introduces a distinct melt flow feature during injection molding usually in the packing stage; i.e., the melt flow in the cavity of mold is manipulated by using pressure-driven flow.…”
Section: "Structuring" Polymer Processing Based On Ficpmentioning
confidence: 99%
“…If different types of polymers, or polymers with various colorants and additives, are extruded into a single film, multiple extruders can be fed into one die. Cast film extrusion finds extensive application in producing polypropylene (PP) films for packaging purposes [44][45][46]. Additionally, extrusion is commonly employed in manufacturing polytetrafluoroethylene and other fluorinated polymer membranes.…”
Section: Extrusionmentioning
confidence: 99%
“…According to literature review, grafting side branches in the form of hydrocarbon or functional groups to the polymer chain of polyolefins has a direct effect on the adhesion strength of these materials. [ 13 ] The results indicated that the structural factors which affect the heat sealing of polymers are the possibility of penetration of polymer chains into the interface of two polymeric surfaces in contact with each other, the possibility of chemical reaction between chains, and the possibility of crystallization. Meanwhile, the use of the reactive melt mixing method and the possibility of chemical reactions occurring during the forming process in the molten state, taking into account the major advantages such as economic efficiency and the possibility of industrialization, the ease of carrying out the process, and high efficiency, the importance of using this method as an alternative other methods are noted.…”
Section: Introductionmentioning
confidence: 99%